Comparative foundations of a European law of set-off and prescription - Zimmermann, Reinhard (Cambridge University, 2013)
European private law is becoming an increasingly important legal issue. Professor Zimmermann considers the two complex and neglected topics of set-off and prescription in ten European legal systems, concluding each essay with a model for a common European approach. This will interest all comparative lawyers and legal historians.